A postpositivist commentary on self-fulfilling theories - Shadnam, Masoud (My University, 2019)
Across the vast terrain of social and economic sciences, it is well documented and established that some theories become self-fulfilling in the sense that they shape the social reality they purport to describe ([4], [5]; [9]). In their recent article [8] highlight an important gap in this literature—that is, we do not know much about when and how theories become self-fulfilling. Reflecting on this gap, they propose a process model for self-fulfilling theories and identify six boundary conditions that determine whether a theory becomes self-fulfilling or not.
Keywords: expectation (psychology); self-fulfilling prophecy; positivist ethics